(untitled) (Biological Sciences - PJSIR, 1995)
The reaction between ethyl xalate and hydroxide ions was studied in a series of ethanol-water mixtures at 25± 0.1°C to find out the dependence freaction rate on dielectric constant of the medium. Attempts were made to calculate the radii of activated complex fO Single sphere (r") and double sphere (rAB) models from the linear plots of logarithm of rate constant at Zero ionic stre gth (k) against reciprocal of the dielectric constant (1110), in order to find out the most probable shape of the activated c, mplex. A comparison of the experimental values of radii (r") and (rAB) respectively with the theoretical values led to the conclusion that activated complex exists as a double sphere model.